2016
DOI: 10.4102/sajesbm.v8i1.101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of culture on female entrepreneurs in Zimbabwe

Abstract: <strong>Background:</strong> There is an increasing interest in female entrepreneurship, not only to realise the potential for economic growth, but also in light of the opportunities for female expression, emancipation, agency and empowerment. Literature has found that many female entrepreneurs are profoundly affected by the traditional sociocultural context in which they operate, and that they have needed to work around patriarchal barriers in order to succeed. This study explores the ways in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…In other words, relatives of women entrepreneurs often provide monetary contributions or even join the workforce within women-owned enterprises at little or no extra cost (Dana et al, 2020;Neneh, 2017;Thébaud, 2016). Some of their family members also support their access to markets (Jamali, 2009;Mazonde & Carmichael, 2016). On the contrary, there is evidence that motherhood can restrict the growth of women-owned firms, particularly in contexts wherein entrepreneurship is considered a masculine realm (Jamali, 2009;Mazonde & Carmichael, 2016) or where relatives are of the view that women are unlikely to succeed in entrepreneurship (Adom et al, 2018;Azmat & Fujimoto, 2016) and where there are conflicts with women's family-work (Hurley & Choudhary, 2016;Joona, 2018;Okpara et al, 2011).…”
Section: Motherhoodmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, relatives of women entrepreneurs often provide monetary contributions or even join the workforce within women-owned enterprises at little or no extra cost (Dana et al, 2020;Neneh, 2017;Thébaud, 2016). Some of their family members also support their access to markets (Jamali, 2009;Mazonde & Carmichael, 2016). On the contrary, there is evidence that motherhood can restrict the growth of women-owned firms, particularly in contexts wherein entrepreneurship is considered a masculine realm (Jamali, 2009;Mazonde & Carmichael, 2016) or where relatives are of the view that women are unlikely to succeed in entrepreneurship (Adom et al, 2018;Azmat & Fujimoto, 2016) and where there are conflicts with women's family-work (Hurley & Choudhary, 2016;Joona, 2018;Okpara et al, 2011).…”
Section: Motherhoodmentioning
confidence: 99%
“…Some of their family members also support their access to markets (Jamali, 2009;Mazonde & Carmichael, 2016). On the contrary, there is evidence that motherhood can restrict the growth of women-owned firms, particularly in contexts wherein entrepreneurship is considered a masculine realm (Jamali, 2009;Mazonde & Carmichael, 2016) or where relatives are of the view that women are unlikely to succeed in entrepreneurship (Adom et al, 2018;Azmat & Fujimoto, 2016) and where there are conflicts with women's family-work (Hurley & Choudhary, 2016;Joona, 2018;Okpara et al, 2011). In such instances, motherhood could inhibit the growth of women-owned enterprises.…”
Section: Motherhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Woman and Entrepreneurship: There is still minimum research conducted on female entrepreneurship in South Africa and among the developing world (Mazonde and Carmichael, 2016;Brush and Cooper, 2012). Entrepreneur is a French word which dates to the 1700s, and it has been used to refer to someone who undertakes a venture (Herrington, Kew, Kew and Monitor, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding contradicts the results of O'Neill and Viljoen (2001) that South African women are now more accepted as equals, that government policies in South Africa favour women and that women are entering the market at a faster rate than before. Mazonde and Carmichael (2016) interviewed 43 female entrepreneurs in Zimbabwe and the majority of the participants reported that their husbands looked down on their entrepreneurial activities. In an effort to keep their family intact, these women were willing to bow to patriarchy.…”
Section: Development Of Women Entrepreneursmentioning
confidence: 99%